Analisis Tingkat Keselamatan Jalan Tol Berdasarkan Metode Pembobotan Korlantas (Studi Kasus: Jalan Tol Cipularang) - Hanafi, Hanafi; Rusgiyarto, Ferry; Pratama, Rangga (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2019)
Traffic accidents not only caused material losses but the resulted on the loss of very high in human resources. The Cipularang toll road segment has many blackspot locations which is a decrease in the performance of the toll road section. The approach method to accident data analysis with Korlantas ranked. the analysis was to predict the location of the blackspot based on the fatality rate of the accident victims on the road. Based upon the analysis of Korlantas ranked were the high number of accidents is at locations KM 91-93. The aspects reviewed on evaluated blackspot areas included traffic volume, operational speed, geometric, and road equipment. The time of the accident at 00.00-06.00 with an average percentage of 43%, the type of collision was dominated by the accident itself with an average percentage of 37%, based on the factor causing the accident was the lack of anticipation of the driver with an average percentage of 48%. Accidents that often occur occur in KM. 91 by having the highest accident rate dominated by large truck vehicles with an average percentage of 14% and having a high fatality rate of accident victims. The proposed handling of the blackspot area of ​​Cipularang toll road KM 91-93 based on the dominant caused of the accident was carried out on an effort to improve road safety.